2011
DOI: 10.1017/s0079497x00000669
|View full text |Cite
|
Sign up to set email alerts
|

Excavations at a Neolithic Enclosure on The Peak, near Birdlip, Gloucestershire

Abstract: Surveys and excavations in 1980–1 confirmed Peak Camp as a Neolithic enclosure on a flat promontory of the Cotswold escarpment overlooking the Severn Valley just 1 km south of Crickley Hill. Although heavily eroded by quarrying the site can be reconstructed as having two concentric arcs of boundary earthworks forming an oval plan which was probably open to the north where a steep natural slope defined the edge of the site. A section through the outer boundary showed four main phases of ditch construction, at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 51 publications
(27 reference statements)
0
22
0
Order By: Relevance
“…Validation of our predictions could be facilitated by expansive geophysical surveys, and paleochannels and geomorphological deposits could also provide a degree of corroboration. Archaeological investigation into Neolithic sites rarely extends beyond the confines of the site itself, thereby neglecting the understanding of the surrounding landscape (Darvill, 2010). Recent broad-scale work, such as at the Early Mesolithic site of Star Carr, was undertaken using vast coring strategies enabled for the extent of an old lake to be elucidated, as well as to track the hydrological and vegetational change that the landscape experienced (Milner et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Validation of our predictions could be facilitated by expansive geophysical surveys, and paleochannels and geomorphological deposits could also provide a degree of corroboration. Archaeological investigation into Neolithic sites rarely extends beyond the confines of the site itself, thereby neglecting the understanding of the surrounding landscape (Darvill, 2010). Recent broad-scale work, such as at the Early Mesolithic site of Star Carr, was undertaken using vast coring strategies enabled for the extent of an old lake to be elucidated, as well as to track the hydrological and vegetational change that the landscape experienced (Milner et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the Early Neolithic, extensive monumentality began to be constructed, i.e., long barrows and causewayed enclosures, which fundamentally changed the way the landscape was characterized and used. These sites have been considered recurrently in numerous syntheses, often focusing upon the typology and physical form of these sites, with little detail paid to the broader landscape and settings of the sites (e.g., Witts, 1883;Crawford, 1925;O'Neil and Grinsell, 1960;Corcoran, 1969;Darvill, 2010).…”
Section: Archaeologymentioning
confidence: 99%
“…Such phenomenon of delayed chronology could of course be repeated in the British Isles and Ireland. The fragment of a perforated schist bracelet found at Peak Camp (Darvill et al 2011), only 10km from the Severn Estuary facing the Irish Sea, clearly refers to an ornament specific of the Early Neolithic period in northwestern France. It alone testifies to this palimpsest that is so difficult to decipher (of course, the similar 'pendentifs arciformes' of the Paris basin are late Neolithic).…”
Section: The Charm Of the Seamentioning
confidence: 99%
“…The presence of natural silting at several of these sites, interspersed with features that may demonstrate the ditches were intermittently recut, could indicate that visits to causewayed enclosures were episodic and may have been seasonal (eg, Smith 1965, 7, 20; Mercer 1988, 94; Mercer & Healy 2008, 755; Pryor 1998, 364; Legge 2008, 554). Archaeological evidence also suggests that many of the artefacts found within the enclosure ditches were selectively deposited and that the butchered remains of cattle, also frequently found within enclosure ditches, could also be associated with feasting activity (eg, Smith 1971, 100; Whittle et al 1999, 357; Evans & Hodder 2006, 319; Mercer & Healy 2008, 755, 762; Darvill et al 2011, 139, 195; Thomas 2016; although see Parmenter et al 2015). The presence of both articulated formal burials and disarticulated human remains within the enclosure ditches demonstrates that these sites were also associated with mortuary rites and the commemoration of the dead (eg, Drewett et al 1977, 225–6; Pryor 1998, 362; Mercer & Healy 2008, 759–60).…”
Section: Archaeological Evidence For Landscape Use and The Role Of Causmentioning
confidence: 99%
“…Analysis of material culture and the derivation of raw materials that were used to manufacture many of the artefacts found at causewayed enclosures, such as pottery and worked stone, has also been employed as a proxy for reconstructing patterns of land use. Causewayed enclosures are frequently located on the slopes of elevated promontories (Oswald et al 2001, 91, 109–10), and are sometimes found in pairs, situated side by side on adjacent spurs of the same hilltop ( ibid ., 112–13; Allen et al 2008; Healy 2008, 3; Darvill et al 2011, 196; Dixon et al 2011, 465). Some researchers suggest that the contrasting form and fabric of artefacts found in adjacent enclosures may indicate that each had a different functional role (Allen et al 2008, 308–12).…”
Section: Archaeological Evidence For Landscape Use and The Role Of Causmentioning
confidence: 99%